Lawsonia Inermis as green inhibitor for corrosion protection of aluminium alloy - W.B., Wan Nik; F., Zulkifli; R.., Rosliza; Rahman, Md. Mokhlesur (http://www.ijmer.com/index.html, 2012)
Corrosion behaviour of aluminium alloy inhibited by henna was investigated by using weight loss analysis, Fourier Transform Infrared (FTIR), electrochemical impedance spectroscopy (EIS) and potendiodynamic polarization study. Lawsonia inermis or also known as henna was extracted by using ethyl acetate and methanol. The result from these characterization shows that henna extracted in ethyl acetate exhibits better inhibition towards corrosion. The value for charge transfer resistance, (Rct) decreases as a result of increasing in the degree of protection of AA5083. Double layer capacitance, (Cdl) decrease indicates that a layer was form indicating the formation of a surface film. This reflects the inhibitor does retard the corrosion rate. Both solvent extract Lawsone component which is the main constituent of Lawsonia Inermis and both also were able to inhibit AA5083 in this experiment.